2020
DOI: 10.1038/s41598-020-74593-w
|View full text |Cite
|
Sign up to set email alerts
|

SPARC promotes insulin secretion through down-regulation of RGS4 protein in pancreatic β cells

Abstract: SPARC-deficient mice have been shown to exhibit impaired glucose tolerance and insulin secretion, but the underlying mechanism remains unknown. Here, we showed that SPARC enhanced the promoting effect of Muscarinic receptor agonist oxotremorine-M on insulin secretion in cultured mouse islets. Overexpression of SPARC down-regulated RGS4, a negative regulator of β-cell M3 muscarinic receptors. Conversely, knockdown of SPARC up-regulated RGS4 in Min6 cells. RGS4 was up-regulated in islets from sparc −/− mice, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…SPARC secreted from adipose tissue could induce ectopic lipid deposition and insulin resistance ( Kos and Wilding, 2010 ), whereas SPARC secreted from pancreatic stellate cells mediates the communication between stromal cells and endocrine cells by regulating β-cell survival ( Ryall et al., 2014 ). SPARC has recently been identified to modulate β-cell glucose sensing through maintaining glucose transporter 2 expression level ( Atorrasagasti et al., 2019 ) and promote insulin secretion via downregulation of RGS4 protein ( Hu et al., 2020 ). ATF3 is involved in glucose metabolism in a variety of organs and tissues, whereas the physiological roles of ATF3 in the pancreas present crucial variances.…”
Section: Discussionmentioning
confidence: 99%
“…SPARC secreted from adipose tissue could induce ectopic lipid deposition and insulin resistance ( Kos and Wilding, 2010 ), whereas SPARC secreted from pancreatic stellate cells mediates the communication between stromal cells and endocrine cells by regulating β-cell survival ( Ryall et al., 2014 ). SPARC has recently been identified to modulate β-cell glucose sensing through maintaining glucose transporter 2 expression level ( Atorrasagasti et al., 2019 ) and promote insulin secretion via downregulation of RGS4 protein ( Hu et al., 2020 ). ATF3 is involved in glucose metabolism in a variety of organs and tissues, whereas the physiological roles of ATF3 in the pancreas present crucial variances.…”
Section: Discussionmentioning
confidence: 99%
“…These can be exploited to both build/optimize animal models and potentially develop therapies (Figure 9). First, we could knockout or knock-down Sparc in order to build animal models (and even cellular models) to explore diseases and health conditions, as well as the pathways shown or suggested to interact with SPARC, such as its intracellular interactions and caspase-8, and in colon cancer cells [9], muscle AMPK signaling [81], integrin-linked kinase [8,26], RGS4 protein in pancreatic β cells [73], transforming growth factor-β1 in renal cell carcinoma [125], and beta-catenin in pulmonary fibroblasts [126]. This will deepen our understanding of the diseases and physiological conditions in which SPARC expression changes, such as cancer, obesity, muscle development, exercise, etc.…”
Section: Discussionmentioning
confidence: 99%
“…However, they also showed that the mice had an impaired insulin-secretion capacity rather than insulin resistance (on HFD) [71]. Such findings point to a type 1 diabetes-like phenotype (rather than type 2 diabetes), especially as it has been suggested that SPARC plays a role in insulin secretion [72] and promotes insulin secretion in pancreatic β cells [73]. Therefore, SPARC deficiency would reduce insulin secretion (independently of insulin resistance) [72].…”
Section: Sparc Ko As Type 1 Diabetes Model?mentioning
confidence: 96%
“…Secreted protein acidic and rich in cysteine (SPARC), also called BM-40 and osteonectine, is a non-collagenous [1] and collagen-binding [2], plays a non-structural role in ECM/bone [3], and has three structural domains with active glycoproteins [4] that was initially reported in bones under another name, osteonectine [1]. Additionally, studies have highlighted its implications in numerous physiological and pathological contexts at different biological levels, including in injuries and wound healing [5][6][7][8], exercise and exercise-induced muscle changes [9][10][11], glucose homeostasis and insulin secretion [12,13], metabolism and energy balance [14,15], regeneration [16], inflammation [17][18][19], cancer [20][21][22][23][24][25], obesity and diabetes [26], fibrillar collagen assembly and extracellular matrix maintenance and remodelling [17,27,28], lipid metabolism [29], immunity [30], myocardial repair and fibrosis [2], and vascular biology [31].…”
mentioning
confidence: 99%